Prognostic value of the triglyceride-glucose index for continuous ambulatory peritoneal dialysis patients - Sheng Wan; Hong Zhu; Da He; Yanglin Hu; Zengsi Wang; Yanmin Zhang (BMC Nephrology)
Abstract Objective We are committed to demonstrating that the initial triglyceride-glucose (TyG) index possesses prognostic importance for patients undergoing continuous ambulatory peritoneal dialysis (CAPD). Methods 354 patients who utilized continuous CAPD at Wuhan No.1 Hospital were recruited. The participants were classified into three unique groups according to the tertiles of the TyG index. The main endpoints were overall and cardiovascular (CVD) mortality, whereas the secondary outcomes were peritonitis, technical failure, and early-onset peritonitis. The association between the TyG index and outcomes utilizing Cox proportional hazard and restricted cubic spline analysis. Results Over a median follow-up of 72 months, 92 patients (26.0%) and 60 patients (16.9%) succumbed to all-cause and CVD mortality, respectively. The three groups exhibited significant differences for all-cause death (16.8% in tertile 1, 24.8% in tertile 2, and 36.4% in tertile 3). After full adjustment, patients with the highest TyG index demonstrated a significantly increased all-cause death relative to those in the lowest tertile (hazard ratio, HR, 2.31, 95% confidence interval, 95%CI 1.18–4.56, P = 0.015). Similarly, each unit increase in the TyG index was associated with a 1.32-fold elevated risk of all-cause death (HR 1.32, 95% CI 1.06–1.87, P = 0.031). Restricted cubic spline analysis indicated a relationship between the TyG index and all-cause mortality (P for nonlinearity > 0.05). Furthermore, the same findings were also seen with CVD mortality and secondary outcomes. Conclusion The TyG index may function as a meaningful and reliable prognostic indicator in CAPD patients, suggesting its potential importance in improving risk stratification in clinical environments.